Virus taxonomy : classification and nomenclature of viruses. Seventh report of the International Committee on Taxonomy of Viruses (Academic Press, 2000)
Universal, unambiguous virus taxonomy (naming and categorization) is vital for distinguishing the thousands of viruses which have been isolated from humans, animals, plants, fungi, bacteria, and archae. Before an official identification and classification system was devised, there was much confusion and duplication of viruses isolated in different labs around the world. The first internationally organized attempts to introduce some order in the bewildering variety of viruses took place at the International Congress of Microbiology held in Moscow in 1966. A committee, later called The International Committee on Taxonomy of Viruses (ICTV), was given the task of developing a single, universal taxonomic scheme for all the viruses. This is the seventh report produced by the ICTV and builds on the accumulated taxonomic data of its predecessors and records the proceedings of the Committee since 1995, including decisions reached at the Tenth International Congress of Virology held in Jerusalem in 1996, and at mid-term meetings in 1997 and 1998. The information is essential for anyone working in the field of virology. Clinicians in diagnostic laboratories, researchers citing viruses in published papers, and virologists in the business industry all must have the most updated virus taxonomy to make the appropriate references. The number of recognized viruses continues to grow with the development of better detection techniques, and the rapid evolution of virus variants. Key Features* The official reference for virus taxonomy and nomenclature* Contains 30% new taxa, including two major new contributions on the phylogenetic relationships between viruses, and application of the virus species concept throughout the virus world* Compiles information from 300-400 experts* Covers over 4000 recognized viruses, organized by family, with diagrams of genome organization and virus replication cycle where know* Includes over 300 figures and illustrations
Keywords: Viruses; virologie; viry